Single-Chain Soluble Receptor Fusion Proteins as Versatile Cytokine Inhibitors - Holgado, Aurora; Braun, Harald; Verstraete, Kenneth; Vanneste, Domien; Callewaert, Nico; Savvides, Savvas N.; Afonina, Inna S.; Beyaert, Rudi (Frontiers in Immunology, 2020)
Cytokines are small secreted proteins that orchestrate inflammation in host defence and disease. In the past years, a large number of biologics have been developed to target cytokines in disease, amongst which soluble receptor fusion proteins have shown some promise in pre-clinical studies. We have previously shown proof-of-concept for the therapeutic targeting of interleukin (IL)-33 in airway inflammation using a newly developed biologic, IL-33trap, which is a single-chain recombinant fusion protein of the soluble IL-33 receptor ST2 and its soluble co-receptor IL-1RAcP. Here we focus on its further biophysical and biological characterisation, showing that IL-33trap is a biophysically stable molecule with a monomeric profile both at physiological temperatures and during liquid storage at 4 °C. Reducing the N-glycan heterogeneity and complexity of IL-33trap via GlycoDelete engineering does not affect IL-33trap stability and IL-33 inhibitory activity. We also report that IL-33trap specifically targets biologically active IL-33 splice variants. Finally, we document the generation and antagonistic activity of a single-chain IL-4/13trap, which inhibits both IL-4 and IL-13 signalling. Altogether, these results illustrate that single-chain soluble receptor fusion proteins against IL-4, IL-13, and IL33 are novel biologics that are not only of interest for research purposes, but may also complement monoclonal antibodies for the treatment of allergic and other inflammatory diseases.